Impact of OH Radical Generator Involvement in the Gas‐Phase Radical Reaction Network on the Oxidative Coupling of Methane—A Simulation Study. Issue 8 (17th July 2019) - Li, Duanxing; Baslyman, Walaa S.; Sarathy, S. Mani; Takanabe, Kazuhiro
Abstract : The impact of OH generation during the oxidative coupling of methane (OCM) is simulated using state‐of‐the‐art gas‐phase chemistry and a comprehensive chemical kinetic model. The inclusion of the quasi‐equilibrated formation of OH from a H2 O–O2 mixture into the combustion chemistry network enhances the CH4 conversion rate and C2 selectivity, consistent with the previously proposed mechanism involving catalytically generated OH . The OH‐pathway increases the CH 3 concentration resulting in an enhanced transformation rate from CH 3 to C2 H6 (second order in CH 3 ) more than CO (first order in CH 3 ). Relative to other H‐abstracting radical species, the OH weakens the sensitivity of the H abstraction rate constant to C—H bond energy, or lowers k C 2 H 6 / k CH 4, which comparatively slows the C2 H6 conversion rate relative to CH4, thus enhancing C2 selectivity. Concurrent dehydrogenation of C2 H6 to C2 H4 maximizes the C2 H4 selectivity even after O2 depletion. With the involvement of the OH ‐mediated pathway, this study addresses the effects of temperature and CH4 /O2 ratio on the achievable C2 selectivity and C2 H4 yield. The maximum C2 H4 yield reaches 32% at a CH4 /O2 ratio of 3, temperature of 1100–1200 °C, and total pressure of 1 atm. Abstract : The different extent of OH radicals generated from a O2 –H2 O mixture is integrated to the state‐of‐the‐art radical chemistry to simulate the performance of oxidative coupling of methane (OCM). Such simulation demonstrates the beneficial role of the OH radical for OCM rates and selectivity, predicting the maximum C2 H4 yield to be 32%.